1973
DOI: 10.1080/00103627309366468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen, phosphorus and potassium on yields and nutrient levels in carrots grown on sphagnum peat and mineral soils.

Abstract: Carrots, Daucus carota L., were grown on both sphagnum peat and mineral soils from 1969 to 1972 inclusive. Fertilizer treatments consisted of three rates of N, of P and of K applied in all possible combinations.In practically every instance rates of N, P and K applied to sphagnum peat were reflected in the levels of these nutrients found in carrot leaves. This was not the case with mineral soils.On sphagnum peat there were eight opportunities, and on mineral soils seven, for each of the three applied nutrients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Nitrogen application above 110 kg/ha decreases the yield (Bishop, 1973) and quality due to root cracking (Balvoll, 1995). Large nitrate concentration in soil tends to improve shoot: root ratio (RaynalLacroix, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen application above 110 kg/ha decreases the yield (Bishop, 1973) and quality due to root cracking (Balvoll, 1995). Large nitrate concentration in soil tends to improve shoot: root ratio (RaynalLacroix, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Organically cultivated carrot roots had a higher P content than those of the fertilizer experiment ( Table 2). The P concentration in organically cultivated soils was remarkably higher than in the fertilization experiment (Evers 1988). In the literature, the P content of carrot leaves has been reported to be 0.19-0.27 % DM on mineral soils (Bishop et al 1973) and 0.17-0.21°7o DM (Nilsson 1979). In the study of Nilsson (1979), organic fertilizer in-creased the P content of leaves as compared to mineral fertilizer.…”
Section: Phosphorusmentioning
confidence: 99%
“…1985). In the study of Bishop et al (1973), the K content of carrot shoots and roots was 3.79-5.88 % DM and 2.65-3.06 % DM, respectively. They also found that there were differences between years, particularly in the K content of roots.…”
Section: Potassiummentioning
confidence: 99%
See 2 more Smart Citations